A CRITICAL EXAMINATION OF COMMUNITY HEALTH INTEGRATION INTO HOSPITAL MANAGEMENT - Nasser Hussain Alyami, Hamad Hussain Alirfan, Salem Saleh Bani Humayyim, ‏ Mohammed Abdullah Saeed Alzahrani, Mosfer Saeed Mezher Alkathami , ‏ Abdullah Saad Saeed Alahmari , Adel Mokkeled Almutairi , Ahmed Atlah Ahmed Al Zahrani (Chelonian Research Foundation, 2022)
This article critically examines the integration of community health services into hospital management, a pivotal shift in the healthcare paradigm aimed at fostering holistic and efficient care delivery. Despite the clear benefits, including enhanced patient outcomes and improved accessibility, this integration presents a multifaceted challenge, encompassing administrative, cultural, and financial barriers. Through a comprehensive review of existing literature, case studies, and policy analysis, this paper delineates the current landscape, evidencing the potential of integrated care models while highlighting the substantial obstacles that impede their widespread adoption. The analysis further delves into innovative strategies that have shown promise in bridging the divide between community health services and hospital management, including technological advancements, interdisciplinary training, and policy reforms. Ethical considerations, particularly regarding patient privacy and equity, are also explored to underscore the complexity of implementing integrated healthcare services. The article concludes by positing future directions for research and practice, emphasizing the need for adaptive strategies in the face of emerging healthcare trends and technologies. This critical examination not only sheds light on the challenges and opportunities of integration but also serves as a call to action for stakeholders to collaboratively redefine the contours of effective healthcare delivery. Keywords: Integrated Healthcare Models, Community Health Services, Hospital Management, Healthcare Delivery Systems, Interdisciplinary Collaboration, Healthcare Policy, Technological Innovations in Healthcare, Patient Outcomes.